Sistem Pendukung Keputusan Penentuan Kelayakan Penerima Program Keluarga Harapan Menggunakan Metode TOPSIS - Gilbert Johan Martin Sinaga; William Charlie Septian Sinaga (Universitas Sains Indonesia Publishing, 2026)
The selection of beneficiaries for the Program Keluarga Harapan (PKH) often faces issues of inaccurate targeting due to selection processes that are not fully objective and structured. This study aims to develop a Decision Support System (DSS) using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the eligibility of PKH beneficiaries in Simarimbun Subdistrict, Pematangsiantar City. This research adopts a quantitative approach using primary data collected through questionnaires from 30 potential beneficiaries. The criteria used include education level, income, number of dependents, and housing conditions. The data were processed using the TOPSIS method to generate preference values and rank the alternatives. The results show that the system classified 11 alternatives (36.67%) as eligible and 19 alternatives (63.33%) as ineligible. The developed system provides consistent, criteria-based recommendations, thereby improving objectivity in the beneficiary selection process. This study contributes by providing a structured system-based approach and decision-making method to support more accurate targeting in social assistance distribution.